Advances in human action recognition: an updated survey. Issue 13 (17th October 2019) - Abu‐Bakar, Syed A.R.
Abstract : Research in human activity recognition (HAR) has seen tremendous growth and continuously receiving attention from both the Computer Vision and the Image Processing communities. Due to the existence of numerous publications in this field, undoubtedly, there have been a number of review papers on this subject that categorise these techniques. Many of the recent works have started to tackle more challenging problems and these proposed techniques are addressing more realistic real‐world scenarios. Conspicuously, an updated survey that covers these methods is timely due. To simplify the categorisation, this study takes a two‐layer hierarchical approach. At the top level, the categorisation is based on the basic process flow of HAR, i.e. input data‐type, features‐type, descriptor‐type, and classifier‐type. At the second layer, each of these components is further subcategorised based on the diversity of the proposed methods. Finally, a remark on the coming popularity of deep learning approach in this field is also given.